An overview of financial procedure & position of Kuehne + Nagel Bangladesh Limited - Solaiman, Mahabub Ibn (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.